Web accessibility in Mobile Applications of Education Sector: the accessibility evaluation of mobile apps of higher education sector in Portugal - Liren Su (2021)
The development of science and technology evolution are advancing with each passing day. The number of smartphone users has increased significantly and the development of mobile applications has brought convenience to the daily life. However, large numbers of users who have various barriers, such as visual or hearing impairments, and physical disorders, are not able to fully access and use the referred applications, which is unfair to them, especially when considering its use by students in a university campus where all users should be able to enjoy equal opportunities and experiences. But since the barrier-free development has not kept up with the speed of app development, and many developers are not aware of the special needs of users who have impairments or disorders, students with disabilities cannot fully enjoy the convenience of using those apps as another tool for a successful student life. Hence, this project aimed to explore the weaknesses of mobile applications regarding their accessibility, to generate a set of guidelines that would allow for the above mentioned right to equality to be leveled up, and focus on the particular case of the higher education sector in Portugal. This project starts by presenting an analysis to the existing accessibility guidelines and accessibility testing tools and applications which were already available in the market. The results indicated that there are no proper accessibility standards and guidelines in the market for mobile applications, as the most recognized set of guidelines (WCAG – Web Content Accessibility Guidelines), are mainly focused on computer-based access to Web content. In addition, only five applications were found that perform accessibility testing in mobile applications (two of them are automatic, two are only possible to run in developer mode and the other is quite limited; the rest is similar to a manual test). The document finalizes with a summary of the most common accessibility issues detected in evaluated apps, and with the establishment of accessibility recommendations that should incorporated by mobile application designers, developers.